2003
DOI: 10.1046/j.1469-8137.2003.00689.x
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome‐hormonal signalling networks

Abstract: Contents Summary    449 Introduction    449 The phytochrome protein  450 Bacteriophytochromes   450 IBacteriophytochrome signalling  450 Plant phytochrome signalling  451 Ethylene perception and signalling  451 Cytokinin perception and signalling 452 Brassinosteroid perception and signalling  453 Gibberellin signalling   455 Auxin signalling   456 Proteolysis in light and hormonal signalling  458 Conclusion    459 Acknowledgements   459 References    459 Summary Through time, plants have evolved an extraor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 170 publications
(268 reference statements)
0
75
0
Order By: Relevance
“…Experimental evidence has indicated that classic plant growth hormones, including auxin, brassinosteriods, ethylene and gibberellic acid, are involved in light control of plant development. 2 Nonetheless, the role of ABA in light signaling is much less clear, although light affects the metabolism of ABA 3 and the expression of certain ABA-responsive genes. In a recent study, 4 we reported an interaction between the light signaling pathway and the ABA signaling pathway during seed germination and early seedling development.…”
Section: The Light-signaling Component Hy5 Mediates Aba Response In Smentioning
confidence: 99%
“…Experimental evidence has indicated that classic plant growth hormones, including auxin, brassinosteriods, ethylene and gibberellic acid, are involved in light control of plant development. 2 Nonetheless, the role of ABA in light signaling is much less clear, although light affects the metabolism of ABA 3 and the expression of certain ABA-responsive genes. In a recent study, 4 we reported an interaction between the light signaling pathway and the ABA signaling pathway during seed germination and early seedling development.…”
Section: The Light-signaling Component Hy5 Mediates Aba Response In Smentioning
confidence: 99%
“…There are several hormones (e.g., auxin, brassinosteroids, and gibberellins) involved in cell expansion that are interconnected with light signaling during photomorphogenesis (Halliday and Fankhauser, 2003;Neff et al, 2005). Multiple suppressors of the long-hypocotyl phenotype of phyB mutants have been identified, which are in involved both photomorphogenesis and hormone signaling (Reed et al, 1998;Neff et al, 1999).…”
Section: New Role For the Dof Transcription Factor Obp3 In Light Signmentioning
confidence: 99%
“…Blocking chloroplast development severely impairs light induction of transcription of nuclear genes that encode proteins targeted to the chloroplasts (Surpin et al, 2002). Light in turn affects the circadian clock (Devlin and Kay, 2000), the hormonal status (Halliday and Fankhauser, 2003) and the developmental status of the chloroplasts. Light also modulates the responses to hormones.…”
Section: Interaction Between Light and Other Signalsmentioning
confidence: 99%